Language choice of Malaysian Tamil students in Facebook: a case study in a Malaysian university - Sinayah, Malarvizhi; Perumal, Thanalachime; Maruthai, Elanttamil; Muthusamy, Paramasivam; Muniandy, Ponniamah; Muniandy, Rajantheran (Universiti Putra Malaysia Press, 2017)
Language is a powerful identity of an ethnic group. It is with difficulty that a minority group maintains its mother tongue in a multilingual society, particularly so when other languages such as Malay, English and Chinese have economic advantages over Tamil. Even though in Malaysia Tamil language is taught in primary schools for children aged 7 to 12 and in secondary schools for the students aged 13 to 18, only a few continue to study this language in their higher education. It is a challenge for the educators in higher education institutes to encourage and attract students to study Tamil and is equally challenging to encourage them to maintain Tamil language in their daily conversations. The main aim of this study is to identify the language used in Facebook communication among the Malaysian Tamil students in the university. Reasons for their language choice and some strategies to maintain the usage of Tamil language in social networking platform are also discussed in this paper. Students aged 22 to 24 from a university in the central region of Peninsular Malaysia which offers Tamil studies, are chosen as the participants of this study. The participants were interviewed for their language choice. The finding shows that the participants with excellent Tamil language competency, used code mixing, Romanised Tamil more than Tamil or Tamil script in Facebook communication. This study found a way to make the participants converse solely in Tamil. An altered language behaviour in cyberspace emerging out of unknown consideration, was thwarted and normal language use was restored.